Microbiome-Based Interventions for Food Safety and Environmental Health - Blessing Oteta Simon; Nnabueze Darlington Nnaji; Christian Kosisochukwu Anumudu; Job Chinagorom Aleke; Chiemerie Theresa Ekwueme; Chijioke Christopher Uhegwu; Francis Chukwuebuka Ihenetu; Promiselynda Obioha; Onyinye Victoria Ifedinezi; Precious Somtochukwu Ezechukwu; Helen Onyeaka (Applied Sciences)
The human microbiome plays a critical role in health and disease, with recent innovations in microbiome research offering groundbreaking insights that could reshape the future of healthcare. This study explored emerging methodologies, such as long-read sequencing, culturomics, synthetic biology, machine learning, and AI-driven diagnostics, that are transforming the field of microbiome–host interactions. Unlike traditional broad-spectrum approaches, these tools enable precise interventions, such as detecting foodborne pathogens and remediating polluted soils for safer agriculture. This work highlights the integration of interdisciplinary approaches and non-animal models, such as 3D cultures and organ-on-a-chip technologies, which address the limitations of current research and present ethical, scalable alternatives for microbiome studies. Focusing on food safety and environmental health, we examine how microbial variability impacts pathogen control in food chains and ecosystem resilience, integrating socioeconomic and environmental factors. The study also emphasizes the need to expand beyond bacterial-focused microbiome research, advocating for the inclusion of fungi, viruses, and helminths to deepen our understanding of therapeutic microbial consortia. The combination of high-throughput sequencing, biosensors, bioinformatics, and machine learning drives precision strategies, such as reducing food spoilage and enhancing soil fertility, paving the way for sustainable food systems and environmental management. Hence, this work offers a comprehensive framework for advancing microbiome interventions, providing valuable insights for researchers and professionals navigating this rapidly evolving field.